Reduced cellular susceptibility to in vitro HIV infection is associated with CD4+ T cell quiescence. - Catherine M Card (PLoS ONE, 2012)
HIV preferentially establishes productive infection in activated CD4+ T cells. Since proportions of activated CD4+ T cells vary between individuals, this study aimed to determine if individuals with a greater proportion of activated CD4+ T cells would be more susceptible to in vitro HIV infection.Unstimulated peripheral blood mononuclear cells (PBMC) from various donors were inoculated with HIV(ML1956)in vitro. HIV replication was evaluated by HIV p24 ELISA of culture supernatants and intracellular staining for HIV p24, which was detected by flow cytometry. Baseline T cell phenotypes and infected cell phenotypes were also evaluated by flow cytometry. Ex vivo phenotyping at the time of blood draw showed that elevated T cell activation and reduced Tregs were associated with increased cellular susceptibility to in vitro infection. Furthermore, the infected CD4+ T cell population was enriched for activated cells.These data suggest that CD4+ T cell quiescence provides an environment less conducive to the establishment of HIV infection by limiting the pool of activated target cells.